2014
DOI: 10.3390/molecules190913282
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Relationships between H-Bonding Patterns and Excited State Dynamics in Cyclovalone

Abstract: Cyclovalone is a synthetic curcumin derivative in which the keto-enolic system is replaced by a cyclohexanone ring. This modification of the chemical structure might in principle result in an excited state that is more stable than that of curcumin, which in turn should produce an enhanced phototoxicity. Indeed, although curcumin exhibits photosensitized antibacterial activity, this compound is characterized by very fast excited-state dynamics which limit its efficacy as a photosensitizer. In previous works we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 54 publications
2
15
0
Order By: Relevance
“…There seems to be a difference in emission spectrum and thereby the network Curcumin has been reported to be protonated just below pH 1 followed by an increase in aqueous solubility and a shift in the absorption maximum to 540 nm, as demonstrated in Figure 4. 40 The pH was measured to 0.6 in undiluted MC3 and curcumin should therefore be protonated. However, no spectral change was observed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…There seems to be a difference in emission spectrum and thereby the network Curcumin has been reported to be protonated just below pH 1 followed by an increase in aqueous solubility and a shift in the absorption maximum to 540 nm, as demonstrated in Figure 4. 40 The pH was measured to 0.6 in undiluted MC3 and curcumin should therefore be protonated. However, no spectral change was observed.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…36 Absorption in this wavelength range is ascribed to the conjugation between the aromatic rings in curcumin via the enol-form involving an intramolecular H-bond and the planar conformation of the molecule(Figure 1) 37,38. The absorption maximum at 370 nm can be ascribed to the formation of the polar diketo conformer of the curcumin molecule which leads to a substantial reduction in conjugation (Figure 1) 39,40. That NADES may induce conformational changes in solubilized phenolic compounds has also been observed byDai et al (2014) 41.…”
mentioning
confidence: 96%
“…However, cyclovalone was extremely photolabile, thus CURC resulted a more performing photosensitizer even at moderate light doses [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Various MACs have been synthesized in an attempt to improve the biological activity and other properties [3][4][5][6][7][8]. The recent study reported that AMACs containing a morpholine Mannich base substituted into the phenolic ring and various substituents at para position on another phenyl ring exhibited low antioxidant activity, whereas the compounds containing methoxy or fluoro substituents at the para position on another phenyl ring exhibited potent anti-inflammatory activity that was almost comparable to that of the standard, diclofenac sodium [9].…”
Section: Chemistrymentioning
confidence: 99%
“…Several series of symmetrical monocarbonyl analogs of curcumin (MACs), containing a cyclohexanone or cyclopentanone linker between the two phenyl rings, reportedly have superior anti-inflammatory and antioxidant activity, higher chemical stability, and improved pharmacokinetic profiles compared to curcumin [3,4]. On the other hand, several asymmetrical MAC (AMACs) reportedly exhibit potent anti-inflammatory, antioxidant, and antitumor activities [5][6][7][8]. Finally, our group reported that, while AMACs containing a morpholine Mannich base exhibit low antioxidant activity, two compounds exhibit potent anti-inflammatory activity [9].…”
Section: Introductionmentioning
confidence: 99%